2004
DOI: 10.1002/crat.200310256
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photoluminescence from TlGaS2 layered single crystals

Abstract: Photolimuniscence (PL) spectra of TlGaS2 layered crystals were studied in the wavelength region 500-1400 nm and in the temperature range 15-115 K. We observed three broad bands centered at 568 nm (A-band), 718 nm (B-band) and 1102 nm (C-band) in the PL spectrum. The observed bands have half-widths of 0.221, 0.258 and 0.067 eV for A-, B-, and C-bands, respectively. The increase of the emission band half-width, the blue shift of the emission band peak energy and the quenching of the PL with increasing temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…[46][47][48][49][50][51][52][53][54] They show that the Raman shift can be successfully modeled by including the Table 1. Wavenumber and assignments of the phonon modes observed in the Raman spectrum of MX 2 single crystal using reference [13,[22][23][24][25][26][27] [29,[38][39][40] thermal expansion coefficient, [41,42] effects of thermal expansion and phonon-phonon coupling.…”
Section: Analysis Of Anharmonicity By Raman Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48][49][50][51][52][53][54] They show that the Raman shift can be successfully modeled by including the Table 1. Wavenumber and assignments of the phonon modes observed in the Raman spectrum of MX 2 single crystal using reference [13,[22][23][24][25][26][27] [29,[38][39][40] thermal expansion coefficient, [41,42] effects of thermal expansion and phonon-phonon coupling.…”
Section: Analysis Of Anharmonicity By Raman Spectramentioning
confidence: 99%
“…Wavenumber and assignments of the phonon modes observed in the Raman spectrum of MX 2 single crystal using reference [13,[22][23][24][25][26][27] [29,[38][39][40] thermal expansion coefficient, [41,42] effects of thermal expansion and phonon-phonon coupling. [49] In an isotropic system (such as cubic crystal), the phonon wavenumber ω = ω(V,T). Therefore, at a fixed pressure the total change in phonon wavenumber due to temperature is expressed as follows:…”
Section: Analysis Of Anharmonicity By Raman Spectramentioning
confidence: 99%
“…The lattice of these crystals consists of alternating two dimensional layers arranged parallel to the (001) planes [2]. It has been reported that TlGaS 2 may crystallize in various polytypes due to the attachment of their layers.…”
Section: VImentioning
confidence: 99%
“…In order to investigate the mechanisms governing the material emission, the integrated PL intensity as a function of the temperature inverse, for both pure and doped PVA films, was represented. In order to evaluate the thermal activation energy, the integrated PL intensity of the first three samples, pure PVA, 0.5 and 1 % doped films, was fitted using the Arrhenius model [19][20][21]:…”
Section: Thermal Activation Energiesmentioning
confidence: 99%